Deployment of early diagnosis and mefloquine-artesunate treatment of falciparum malaria in Thailand: the Tak Malaria Initiative. - Carrara, V; Sirilak, S; Thonglairuam, J; Rojanawatsirivet, C; Proux, S; Gilbos, V; Brockman, A; Ashley, E; Mcgready, R; Krudsood, S; Leemingsawat, S; Looareesuwan, S; et al. (Public Library of Science, 2006)
Early diagnosis and treatment with artesunate-mefloquine combination therapy (MAS) have reduced the transmission of falciparum malaria dramatically and halted the progression of mefloquine resistance in camps for displaced persons along the Thai-Burmese border, an area of low and seasonal transmission of multidrug-resistant Plasmodium falciparum. We extended the same combination drug strategy to all other communities (estimated population 450,000) living in five border districts of Tak province in northwestern Thailand.